(untitled) (Journal of Asian Development Studies, 2024)
This study aimed to examine how teachers perceive the diagnostic practices used to identify mathematical learning difficulties among hearing-impaired students. This study adopted a quantitative research design, sampling 300 teachers using simple random sampling. We collected data using a self-developed questionnaire and analyzed the data using descriptive and inferential statistics in SPSS. The study highlights the importance of visual aids, non-verbal assessment, and teamwork between the audiologist and educator to identify hearing-impaired students. Teachers believe that we need to design more versatile tools in addition to norm-referenced tests. This underscores the shortcomings in the diagnostic tools. There was a lack of specialized diagnostic equipment for both hearing and learning disabilities, as reported during the observation. It also highlights the need for continuous practice improvement and excellent collaboration among all stakeholders. These findings contribute to the broader literature on inclusive education and underscore the necessity for innovation in diagnostic tools to support students with hearing impairments better. In this area, emerging technologies should be the focus of further research to improve diagnosis.